Front Cover Picture: Bis‐Alkoxycarbonylation of Acrylic Esters and Amides for the Synthesis of 2‐Alkoxycarbonyl or 2‐Carbamoyl Succinates (Adv. Synth. Catal. 3/2020). Issue 3 (12th December 2019) - Olivieri, Diego; Tarroni, Riccardo; Della Ca', Nicola; Mancuso, Raffaella; Gabriele, Bartolo; Spadoni, Gilberto; Carfagna, Carla
Abstract : The front cover picture, provided by Carla Carfagna et al., shows the first example of an oxidative bis‐alkoxycarbonylation of acrylic esters and acrylic amides, leading to 2‐EWG‐substituted succinates. Despite the low reactivity of electron‐deficient olefins in carbonylation reactions, the aryl α‐diimine palladium(II) catalyst is able to promote the carbonylation of both the β‐ and the generally non‐reactive α‐positions of electron‐poor alkenes, under mild reaction conditions ( P CO =4 bar, T =20 °C). Further details of this work can be found in the full paper on pages 533–544 (D. Olivieri, R. Tarroni, N. Della Ca′, R. Mancuso, B. Gabriele, G. Spadoni, C. Carfagna, Adv. Synth. Catal . 2020, 362, 533–544; DOI: 10.1002/adsc.201900918 ).